A new organ preservation solution for static cold storage of the liver. Amniotic fluid - Büyük,Başak (2019)
Abstract Purpose: To evaluate the effect of amniotic fluid in liver preservation in organ transplantation, and compare it with standard preservation solutions. Methods: The groups consisted of Group 1: Ringer Lactate (RL) group, Group 2: HTK group, Group 3: UW group, Group 4: AF group. The livers of rats from Group 1, 2, 3, and 4 were perfused and placed into falcon tubes containing RL, HTK, UW, and AF solutions at +4‎°C, respectively. The tubes were stored for 12 hours in the refrigerator at +4°C. Tissue samples were taken at the 6th and 12th hours for histopathological examinations of the perfused livers, and storage solutions for biochemical analyzes at 6th and 12th hours. Results: AF was shown to maintain organ viability by reducing the number of cells undergoing apoptosis. Histopathological changes such as sinusoidal dilatation, hydropic degeneration, and focal necrosis were found to be similar to the groups in which the standard organ preservation solutions were used. Additionally, the results of INOS, IL-10, and TNF-α,which were evaluated immunohistochemically, have been shown to be similar to the UW and HTK groups. Conclusions: AF provided conservation similar to UW and HTK in the 12-hour liver SCS process. The fact that apoptosis values are comparable to standard preservation solutions supports the success of AF in the cold storage of the liver.